Scaling of HeatLMD-simulated impurity outflux from COMPASS-U liquid metal divertor - J. Horacek; S. Lukes; F. Jaulmes; J. Cecrdle; D. Tskhakaya; M. Komm (Nuclear Fusion)
The liquid metal divertor (LMD) concept offers a promising solution to manage extreme heat loads in plasma devices. This study presents predictive simulations using the HeatLMD model for the COMPASS-U tokamak with a full toroidal liquid metal divertor, expected to achieve reactor-relevant divertor heat flux densities. We derive the scaling of the Li|Sn outflux over 7 assumed independent parameters, transferable to other tokamaks. Its transport to LCFS (via ERO2.0) and its radiation (via Aurora and FACIT) predicts acceptably low lithium concentration and negligible plasma cooling. However, for tin, the medium power scenario requires backside cooling beyond the capability of the ITER-like water-cooled divertor, though a temporary heat absorber can approximate this for a 1 s plasma pulse. For incident divertor power exceeding 2 MW and strike point T _e < 10 eV, HeatLMD predicts significant tin plasma radiative disruption.